UCIECZKA JĘZYKA Z REFERENCJI, CZYLI O DOŚWIADCZENIU PRZESTRZENI W POWIEŚCIACH ROBBE-GRILLETA - Szczepan, Aleksandra (Pracowania Humanistycznych Studiów Interdyscyplinarnych WFPiK UAM, 2011)
The essay is concerned with the epistemological aspects of space in early novels (The Erasers, The Voyeur, Jealousy) of Alain Robbe-Grillet, a theorist and author of the French New Novel. The text is divided into three parts. The first one is concerned with space on the plane of a story, especially in The Erasers and The Voyeur. The space of the labyrinth drives the protagonists of these novels to a cognitive deadlock. An unknowable structure of the city composed of similar and recurring streets and buildings in The Erasers or identical houses in The Voyeur makes orientation impossible. The second part presents the functions and signification of description in the New Novel according to theoretic essays of Robbe-Grillet. Afterwards, by an examination of the descriptive technique in Jealousy, the author shows how an ultra-realistic description of space loses its function of representation. The third part of the essay is concerned with the figure of mise en abyme – the literary technique of story within a story. Mise en abyme can also be represented on the plane of the plot by specific objects like mirrors, photos, sculpture etc. which remind or indicate the main structure of the story. Mise en abyme lies in the infinite reflection of two mirrors facing one another. There are several examples of this construction in Robbe-Grillet’s novels; they serve as a way to indicate the void and flat space deprived of meaning. Mise en abyme introduces the problem of an unknowable reality closed in repeated reflections of autoreferring space. The conclusion is that space in Robbe-Grillet’s novels serves to show descriptive possibilities of language and their cognitive failure in the paradigm of realism.
Language freed from reference. On experiencing space in Alain Robbe-Grillet’s novels
Keywords: Realizm; Realism; Referencja; Reference; Przestrzeń; Space; Robbe-Grillet